A study of smartphone companies: Do innovation culture and radical innovation affect institutionalization and sustainable competition positively? - Adıgüzel, Zafer; Sönmez Çakır, Fatma; Kalyar, Masood Nawaz (Universidade Nove de Julho (Uninove), 2022)
Objective of the study: The present study examines how innovation culture and radical innovation elicit sustainable competition. The study proposes institutionalization as an important underlying mechanism that originates from innovation culture and radical innovation and provides the basis for sustainable competition. Design/methodology/approach: The data were collected from 763 employees working in smartphone companies located in Istanbul, Turkey. The analysis was performed employing PROCESS macro in order to test the hypothesized relationships. Findings: Results show that both innovation culture and radical innovation have a positive impact on institutionalization and sustainable competition. Moreover, the data also support the mediation effect of institutionalization in predicting sustainable competition. Practical implications: The findings imply that the structure of the firms must be ready for change in order to reap the benefits of sustainable competition. In fact, the creation of an innovation culture is very important in technology-intensive firms because there is a need to create common values that encourage employees to adopt innovative behaviors for sustainable competition. Furthermore, radical innovation can be more advantageous for firm-outcomes when large structural differences are identified and bridged successfully. Originality/value: The study develops a novel framework of innovation-competition using a structural perspective, empirically testing the proposed relationships using data from the technology-intensive industry of Turkey.

Objetivo: O presente estudo examina como a cultura de inovação e a inovação radical geram competição sustentável. O estudo propõe a institucionalização como importante mecanismo subjacente, que se origina tanto da cultura da inovação quanto da inovação radical, e fornece a base para uma competição sustentável. Projeto/metodologia/abordagem: Os dados foram coletados de 763 funcionários que trabalham em empresas de telefonia móvel, localizadas em Istambul, Turquia. A análise foi realizada utilizando a macro PROCESS para testar os relacionamentos hipotetizados. Resultados: Os resultados mostram que tanto a cultura da inovação quanto a inovação radical têm impacto positivo na institucionalização e na competição sustentável. Além disso, os dados também apoiaram o efeito de mediação da institucionalização na previsão da competição sustentável. Implicações práticas: As descobertas implicam que a estrutura das empresas deve estar pronta para mudanças para colher os benefícios da competição sustentável por meio da inovação radical e da cultura de inovação. A criação de uma cultura de inovação é muito importante em empresas intensivas em tecnologia, pois é necessário criar valores comuns para incentivar os funcionários a comportamentos inovadores para competições sustentáveis. A inovação radical pode ser mais vantajosa para os resultados da empresa quando grandes diferenças estruturais são identificadas e superadas com sucesso. Originalidade/valor: O estudo desenvolve uma nova estrutura de inovação-competição usando perspectiva estrutural e testa empiricamente as relações propostas usando dados da indústria intensiva em tecnologia da Turquia.

Objetivo: El presente estudio examina cómo la cultura de la innovación y la innovación radical provocan una competencia sostenible. El estudio propone la institucionalización como un mecanismo subyacente importante, que se origina tanto en la cultura de la innovación como en la innovación radical, y proporciona la base para una competencia sostenible. Diseño/metodología/enfoque: Los datos se recopilaron de 763 empleados que trabajan en empresas de telefonía móvil, ubicadas en Estambul, Turquía. El análisis se realizó empleando la macro PROCESO para probar las relaciones hipotetizadas. Hallazgos: Los resultados muestran que tanto la cultura de la innovación como la innovación radical tienen un impacto positivo en la institucionalización y la competencia sostenible. Además, los datos también respaldaron el efecto mediador de la institucionalización en la predicción de la competencia sostenible. Implicaciones prácticas: Los resultados implican que la estructura de las empresas debe estar preparada para el cambio a fin de cosechar los beneficios de la competencia sostenible a través de la innovación radical y la cultura de la innovación. La creación de una cultura de innovación es muy importante en las empresas intensivas en tecnología porque existe la necesidad de crear valores comunes para alentar a los empleados hacia un comportamiento innovador para competencias sostenibles. La innovación radical puede ser más ventajosa para los resultados de la empresa cuando se identifican y superan con éxito grandes diferencias estructurales. Originalidad/valor: el estudio desarrolla un marco novedoso de innovación-competencia utilizando una perspectiva estructural y prueba empíricamente las relaciones propuestas utilizando datos de la industria intensiva en tecnología de Turquía.
Um estudo sobre empresas de smartphones: A cultura da inovação e a inovação radical afetam positivamente a institucionalização e a competição sustentável?
Un estudio de empresas de teléfonos inteligentes: ¿la cultura de innovación y la innovación radical afectan positivamente la institucionalización y la competencia sostenible?
Keywords: Innovation Culture; Radical Innovation; Institutionalization; Sustainable Competition; Cultura de Inovação; Inovação Radical; Institucionalização; Competição Sustentável; Cultura de Innovación; Innovación Radical; Institucionalización; Competencia Sostenible